Bargaining power in the European Union: an evaluation of competing game-theoretic models - Schneider, Gerald; Finke, Daniel; Bailer, Stefanie (Political studies, 2010)
This article evaluates, by drawing on Barry's distinction between ‘power’ and ‘luck’, the predictive accuracy of competing bargaining models. We explore whether models that take various facets of political power into account predict legislative outcomes more precisely than purely preference-based models like the Nash Bargaining Solution (NBS). Our empirical examination compares how well different formal models predict the outcome of 66 legislative decisions made within the European Union (EU). A model that considers the saliency actors attach to a contested issue performs best among all the models under examination. Although resource-based models provide less accurate forecasts on average, they offer relatively precise point predictions. The analysis also shows that domestic constraints are not a particularly important bargaining resource in legislative decision making.